PROJECT PLANNING PEMBANGUNAN PROYEK JALAN PENGHUBUNG PENYINGGAHAN–MUARA PAHU KUTAI BARAT PROVINSI KALIMANTAN TIMUR - Yanuar Komarudi, Moch. Khamim, Joko Setiono (Prokons: Jurnal Teknik Sipil, 2019)
7.8-km Penyinggahan - Muara Pahu Connecting Road Kutai Barat experienced delays. The purpose of this thesis is to anticipate the delays by making an alternative project planning consisting of a site layout, a cost estimate, an implementation method, a schedule, quality management, and safety, health and environment  (SHE) planning.The required data were of the existing site layout of the project, shop drawings, cost and estimate, work and material unit price of Kutai Barat 2016. MS Project 2007 was applied for scheduling, Autocad 2007 for drawing the site layout, MS Excel for estimating.The planning results in (1) an efficient site layout including a direction kit 3.5km from project location; (2) an implementation method by forwarding critical works like mobilization;(3) 240 calendar days; (4) at Rp._48,257,108,000.00 (5) a quality management system by inspection and testing each stage of work; (6) planning SHE referring to the aspects of SHE and identifying the risks referring to Risk Assessment Matrix (RAM) for each work . Keywords: site layout, implementation method, cost estimate, scheduling, quality  management,  SHE